POLA KONSUMSI BBM ANGKUTAN JALAN RAYA (STUDI KASUS: KOTA YOGYAKARTA, SEMARANG, DAN SURAKARTA) - , PUTRA ABU SANDRA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The usage of motorized vehicles in large volumes, especially in Indonesia, will emerge a problem in terms of fuel consumption. The needs of fuel consumption in transportation sector currently has absorbed more than half of total fuel consumption in Indonesia which dominated by road transport. The aims of this research is to determine how the condition of the fuel consumption in the last 5 (five) years, to study how the contribution of fuel consumption by each type of urban road transport, and to analyze how the pattern of fuel consumption in each city and about relation between energy transport needs and regional domestic income (GDP) and also the relation between fuel consumption and city size. The research is conducted by using primary data which are obtained from field survey in three location and secondary data which are collected from instantional survey. The data analysis is conducted to determine the average fuel consumption by each vehicle type, and then to get the total fuel consumption of each type of vehicle and the total of all fuel consumption. The subsequent analysis is multiple linear regression to find the pattern of fuel consumption by each types of vehicle in urban road transport and simple linear regression and polynomial to find the relationship between the energy consumption by urban road transport and regional domestic income (GDP) and also to find out the relationship between the energy consumption by urban road transport and city size. The results indicate that the energy consumption in the city of Yogyakarta, Semarang and Surakarta have increased each year with the percentage growth 7.43% and the type of vehicles that dominate the energy consumption are motorcycles and private cars. Regression analysis between fuel consumption by each type of road transport and the realization of the total fuel consumption produces a fuel consumption pattern equation. The similarities between the pattern of fuel consumption and total fuel consumption of each type of fuel consumption by road transport in Yogyakarta, Semarang and Surakarta are: Y = 1,33 . (29784,44+ 0,260 X1 +1,001 X2 + 1,70X3 +4,24X4 )......................................Yogyakarta Y = 1,15 (36983,62 +0,25X1 +0,81X2 +2,16X3 +3,96X4 + 6,99X5).................................Semarang Y = 1,30 (17760,54 + 0,24X1 +1,32X2 +3,57X3 +8,81X4 +11,33X5).............................Surakarta The equation of energy consumption pattern in Yogyakarta just comprised of 4 (four) variables, while in the city of Semarang and Surakarta are X5 variables which are public transportation .The results also shows that the GDP of transports and communications sector is more appropriately used to determine fuel consumption by road transport compared to the total GDP of all sectors and city size can be a contributing factor in knowing the total fuel consumption in the city of Yogyakarta, Semarang and Surakarta.